2014
DOI: 10.1111/jsm.12482
|View full text |Cite
|
Sign up to set email alerts
|

An Increased Arginase Activity Is Associated with Corpus Cavernosum Impairment Induced by Hypercholesterolemia

Abstract: Introduction Hypercholesterolemia is a prevalent risk factor for the development of erectile dysfunction (ED), mostly due to an increase in oxidative stress and impaired nitric oxide (NO) bioavailability within the penis. Arginase is an enzyme that shares the common substrate L-arginine with NO synthase. Augmented arginase activity reduces NO production and is associated with ED development. However, the contribution of arginase hyperactivity in hypercholesterolemia-induced ED is unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Studies in humans and animals have suggested a link between increased cavernosal arginase activity and erectile dysfunction [16, 56, 57]. Inhibition of arginase enhances relaxation of cavernosal smooth muscle cells [58, 59]. Whereas NO production from the endothelium and nitrergic nerves regulates intrinsic tone, arginase activity in CC modulates tone by inhibiting NO production, presumably by competiting with NOS for L-arginine.…”
Section: Arginase In Cardiovascular Diseasementioning
confidence: 99%
“…Studies in humans and animals have suggested a link between increased cavernosal arginase activity and erectile dysfunction [16, 56, 57]. Inhibition of arginase enhances relaxation of cavernosal smooth muscle cells [58, 59]. Whereas NO production from the endothelium and nitrergic nerves regulates intrinsic tone, arginase activity in CC modulates tone by inhibiting NO production, presumably by competiting with NOS for L-arginine.…”
Section: Arginase In Cardiovascular Diseasementioning
confidence: 99%
“…L-arginine is described as one of the most abundant free amino acid in onion (Hansen, 2001). It has also been reported that plasma arginine levels are strongly related to the severity of inflammation (van Waardenburg, de Betue, Luiking, Engel, & Deutz, 2007), and arginase hyperactivity may be associated with hypercholesterolaemia (Fraga-Silva et al, 2014). A decreased arginine plasma concentration in the HC-fed rats was also found, while in HCO-fed rats the arginine plasma concentration was increased, reaching the C levels.…”
Section: Discussionmentioning
confidence: 87%
“…Erectile dysfunction can occur due to both physiological and psychological reasons including diabetes, kidney disease, chronic alcoholism, multiple sclerosis, atherosclerosis, vascular disease, and neurologic disease [69][70][71][72]. cGMP specific phosphodiesterase inhibitors such as Viagra® have been used to treat erectile dysfunction by suppressing cGMP and extending erection time.…”
Section: Optogenetic Network For the Treatment Of Penile Erectionmentioning
confidence: 99%